2019
DOI: 10.3389/fphys.2019.00070
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Oxidative Stress and Endoplasmic Reticulum (ER) Stress in Endothelial Dysfunction and Aberrant Angiogenesis Associated With Diabetes: A Focus on the Protective Roles of Heme Oxygenase (HO)-1

Abstract: Type-2 diabetes prevalence is continuing to rise worldwide due to physical inactivity and obesity epidemic. Diabetes and fluctuations of blood sugar are related to multiple micro- and macrovascular complications, that are attributed to oxidative stress, endoplasmic reticulum (ER) activation and inflammatory processes, which lead to endothelial dysfunction characterized, among other features, by reduced availability of nitric oxide (NO) and aberrant angiogenic capacity. Several enzymatic anti-oxidant and anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 175 publications
(221 reference statements)
2
109
0
1
Order By: Relevance
“…Frontiers in Neuroscience | www.frontiersin.org and biliverdin (Rochette et al, 2018;Maamoun et al, 2019). In murine models of doxorubicin (DOX) and ischemia/reperfusion (I/R)-induced cardiomyopathy, administering DOX to mice induced cardiomyopathy with a rapid, systemic accumulation of non-heme iron via heme degradation by Nrf2-mediated upregulation of HO-1, which effect was abolished in Nrf2deficient mice (Fang et al, 2019).…”
Section: Nadph Regenerationmentioning
confidence: 99%
“…Frontiers in Neuroscience | www.frontiersin.org and biliverdin (Rochette et al, 2018;Maamoun et al, 2019). In murine models of doxorubicin (DOX) and ischemia/reperfusion (I/R)-induced cardiomyopathy, administering DOX to mice induced cardiomyopathy with a rapid, systemic accumulation of non-heme iron via heme degradation by Nrf2-mediated upregulation of HO-1, which effect was abolished in Nrf2deficient mice (Fang et al, 2019).…”
Section: Nadph Regenerationmentioning
confidence: 99%
“…Heme Oxygenase-1, a 32 kDa protein, known as heat shock protein-32 (HSP32), is responsible for the degradation of haem with the formation of carbon monoxide (CO), biliverdin and free iron. Similar to HSP70, HO-1 is the stress-inducible isoform of the three HO isoforms described to date, providing a critical protective mechanism in avian systems responsible for adaptation to oxidative, inflammatory and cytotoxic stress [136,137]. In most tissues HO-1 is expressed at a relatively low house-keeping level and it can be induced by various oxidative stress-related insults including haem, ultraviolet light, heavy metals, cytokines, hydrogen peroxide, nitric oxide (NO) and glutathione depletion [138,139].…”
Section: Heme Oxygenase-1mentioning
confidence: 99%
“…We previously showed that miR-494 is responsive to radiation and chemical inducers of genotoxic stress and functions to increase endothelial senescence during DNA damage responses (24). Given the intricate relationship between radiation, oxidative stress and ER stress (14,17), we asked if ER stress affected miR-494 expression and function. First, we confirmed a robust ER stress response to known inducers, tunicamycin (TCN) and thapsigargin (TG), in human umbilical vein endothelial cells (HUVECs) by measuring the level of the transcription factors spliced XBP1 (mRNA: sXBP1, protein: XBP1s) and DDIT3 (CHOP), which are well characterized markers of the ER stress response ( Fig.…”
Section: Er Stress Induces Mir-494 In Vitromentioning
confidence: 99%
“…Furthermore, ER stress has been shown to contribute to vascular dysfunction and cardiac damage in preclinical models of hypertension (11). Similarly, oxidative stress and ER stress pathways have been shown to be interlinked in ECs in metabolic syndromes such as diabetes and non-alcoholic fatty liver disease (NAFLD) (12)(13)(14)(15)(16). Therefore, ECs have adopted several mechanisms to regulate cell fate decisions in response to both acute and chronic ER stress (17).…”
Section: Introductionmentioning
confidence: 99%